The Jurisprudential Preferences of al-ʿAllāmah Qarah Sinān (d. 852 AH) in the Book of Fasting from His Work Riʿāyat al-Wiqāyah Sharḥ Wiqāyat al-Riwāyah: A Comparative Study - Hama Baqi, Youssef (Jordan Journal of Islamic Studies, 2025)
The study focuses on a scholar from the Ḥanafī school of jurisprudence, highlighting his scholarly status among jurists, as well as the significance of his book and the original source upon which he based it. It also provides a comprehensive account of his methodology in authorship and his jurisprudential preferences regarding fasting. Objectives: Studying jurisprudential issues related to fasting is an intellectual journey that contributes to strengthening a Muslim's faith, enhancing their religious awareness, and helping them become a good role model within their community. Method: The study adopts a comparative approach by identifying the expressions used in his juristic preferences, clarifying his opinion on each issue, comparing it with the positions of other schools of thought, discussing their evidence, and stating the preferred opinion. Results: Qarah Sinān was a Ḥanafī jurist known by two titles: "Sīnān al-Dīn" and "Qarah (or Qarā) Sinān." He was also attributed with two nisbahs: "al-Turkī" and "al-Rūmī." His book is of significant value due to the importance of its base text (Wiqāyat al-Riwāyah) in the Ḥanafī school. Most of the sources he relied on in his work remain unpublished and unedited. He predominantly employed rational evidence in his arguments and used specific expressions to indicate his preferences. His juristic choices in the chapter on fasting generally remained within the Ḥanafī school, although he sometimes cited the opinions of Imams Mālik and al-Shāfiʿī to support his views.